2021
DOI: 10.3389/fneur.2021.713738
|View full text |Cite
|
Sign up to set email alerts
|

From Three-Months to Five-Years: Sustaining Long-Term Benefits of Endovascular Therapy for Ischemic Stroke

Abstract: Background and Purpose: During the months and years post-stroke, treatment benefits from endovascular therapy (EVT) may be magnified by disability-related differences in morbidity/mortality or may be eroded by recurrent strokes and non-stroke-related disability/mortality. Understanding the extent to which EVT benefits may be sustained at 5 years, and the factors influencing this outcome, may help us better promote the sustenance of EVT benefits until 5 years post-stroke and beyond.Methods: In this review, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…However, procedural and imaging features only showed a limited impact on favorable outcome rates within the 3-month FU period. These findings indicated that, for a longer time horizon post-stroke survival, age, comorbidities, and physical fitness are of the utmost importance [22], and periprocedural features are less so. Further, as currently reported for common LVO AIS patients [23], very old TL patients (>79 years) were much more likely to die within the follow-up period, which raises the question of how aggressively an EVT treatment should be utilized in this group of patients [24].…”
Section: Discussionmentioning
confidence: 93%
“…However, procedural and imaging features only showed a limited impact on favorable outcome rates within the 3-month FU period. These findings indicated that, for a longer time horizon post-stroke survival, age, comorbidities, and physical fitness are of the utmost importance [22], and periprocedural features are less so. Further, as currently reported for common LVO AIS patients [23], very old TL patients (>79 years) were much more likely to die within the follow-up period, which raises the question of how aggressively an EVT treatment should be utilized in this group of patients [24].…”
Section: Discussionmentioning
confidence: 93%
“…Although some patients' short-term outcomes have improved thanks to EVT, nothing is known about how this surgery would affect patients' quality of life and level of handicap over the long term. [10,11] The usefulness of EVT in preventing impairment and enhancing quality of life in ABAO patients over the long term should be evaluated by additional research. Several factors, including age, stroke severity, time from reperfusion to onset, infarct volume before treatment, thrombosis length, etiology, and collateral circulation, may affect the clinical prognosis of ABAO patients after EVT.…”
Section: Introductionmentioning
confidence: 99%
“…Beside of early outcomes, MT also results in favorable outcomes at long-term follow-up compared to standard medical treatment alone. However, prospective follow-up data from MT trials indicate that 3-month MT benefits will likely translate into lower long-term mortality and disability (with about 31–36% of functionally disabled patients 5 years post-stroke), but these group-level data by no means guarantee maintenance of 3-month positive outcome for individual patients ( 9 ). Several critical factors operate in the post-stroke period that can influence long-term recovery of the patient, and the benefits depend on continuing and optimizing stroke prevention, access to rehabilitation, and post-stroke depression care.…”
Section: Introductionmentioning
confidence: 99%